2012
DOI: 10.2147/ijn.s35190
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bacteria activity on Si3N4 surfaces compared with PEEK or titanium

Abstract: A significant need exists for orthopedic implants that can intrinsically resist bacterial colonization. In this study, three biomaterials that are used in spinal implants -titanium (Ti), polyether-ether-ketone (PEEK), and silicon nitride (Si 3 N 4 ) -were tested to understand their respective susceptibility to bacterial infection with Staphylococcus epidermidis, Staphlococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Enterococcus. Specifically, the surface chemistry, wettability, and nanostructured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 75 publications
(97 reference statements)
1
15
0
2
Order By: Relevance
“…A significant amount of interest has been generated over the past decade in functionalizing biomaterial surfaces to be zwitterionic for anti-fouling purposes 12 . A surface where positive and negative charges are intimately mixed allows for extreme hydrophilicity (as observed on the current surface-treated Si 3 N 4 materials); it also prevents bacterial adhesion (as previously reported for AS Si 3 N 4 samples) 13 . Moreover, zwitterated surfaces have also been observed to induce greater apatite formation on titanium alloys 14 .…”
supporting
confidence: 74%
“…A significant amount of interest has been generated over the past decade in functionalizing biomaterial surfaces to be zwitterionic for anti-fouling purposes 12 . A surface where positive and negative charges are intimately mixed allows for extreme hydrophilicity (as observed on the current surface-treated Si 3 N 4 materials); it also prevents bacterial adhesion (as previously reported for AS Si 3 N 4 samples) 13 . Moreover, zwitterated surfaces have also been observed to induce greater apatite formation on titanium alloys 14 .…”
supporting
confidence: 74%
“…Moreover, the disease has been associated to specific immunological alterations on peri-implant crevicular fluid levels of proinflammatory, anti-inflammatory and osteoclastogenesis-related chemokines [65]. Several studies analyzed in this review [30][31][32][33][34][35] investigated biofilm and antimicrobial properties of pure PEEK, demonstrating that the polymer is susceptible to biofilm colonization. Within a context in which PEEK clinical applications in Implant Dentistry are increasing [28], strategies to modify its surface to enhance its antimicrobial/antibiofilm properties are crucial.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo (human) studies did not fulfill inclusion criteria of this review. Regarding PEEK modification strategies, 6 studies analyzed pure PEEK compared to other materials [30][31][32][33][34][35] (e.g., titanium, silicon, gold, silver, zinc oxide, zirconia, silicon nitride) and none of them revealed special antibiofilm or antimicrobial properties of PEEK material. A total of 25 studies used strategies to reduce biofilm and bacterial colonization on PEEK, which were able to successfully confer either antibiofilm or antimicrobial properties, or both, to the material.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…1923 Materials with different functional groups change bacterial adhesion depending on material hydrophobicity and charge. 24 For example, Chu and Williams studied the effects of physical configurations of suture materials on bacterial adhesion. 25 They showed that polydioxanone sutures exhibited slight affinity towards the adherence of Escherichia coli and Staphylococcus aureus ; however, Dexon sutures had much higher affinity towards the two bacteria.…”
Section: Introductionmentioning
confidence: 99%